Notices (Blackfriars, 1934)
On Being and Essence. By St. Thomas Aquinas. Translated by Clare C. Reidl, M.A. Latinin Church: Episodes in the Hisory of Its Pronunciation, especially in England. By F. Brittain, M.A. Oecumenica. Revue de Synthése theologique trimestrielle. Towards the clerical-Religious Life. By Ralph Damian Goggins, O.P. Kors oc Kanoner. By H. D. T. Kiaerulff. De Valera, By Denis Gwynn. Picaro. By Rupert Croft-Cooke. Freemasonry, a Candid Examination, by a Past Master, (Washbourne and Bogan, 3/6) gives useful information besides dispelling some of the glamour.